Remittances and Vulnerability to Poverty in Rural Mexico - De La Fuente, Alejandro (2012)
Remittances have been portrayed as the human face of globalization given their potential to alleviate poverty by directly increasing household income. Using a panel of rural households in Mexico from October 1998 to November 2000 this study assesses whether this is in fact the case. However, rather than examining whether remittances income would reduce future consumption poverty we asked if remittances are likely to reach people whose conditions are prone to worsen in the future. We found a negative and statistically significant relationship between the disbursement of remittances and the threat to future poverty that rural households could experience.